Nitrous Oxide Induces Prominent Cell Proliferation in Adult Rat Hippocampal Dentate Gyrus - Chamaa, Farah; Bahmad, Hisham F.; Makkawi, Ahmad-Kareem; Chalhoub, Reda M.; Al-Chaer, Elie D.; Bikhazi, George B.; Nahas, Ziad; Abou-Kheir, Wassim (Frontiers in Cellular Neuroscience, 2018)
The identification of distinct and more efficacious antidepressant treatments is highly needed. Nitrous oxide (N2O) is an N-methyl-D-aspartic acid (NMDA) antagonist that has been reported to exhibit antidepressant effects in treatment-resistant depression (TRD) patients. Yet, no studies have investigated the effects of sub-anesthetic dosages of N2O on hippocampal cell proliferation and neurogenesis in adult brain rats. In our study, adult male Sprague-Dawley rats were exposed to single or multiple exposures to mixtures of 70% N2O and 30% oxygen (O2). Sham groups were exposed to 30% O2 and the control groups to atmospheric air. Hippocampal cell proliferation was assessed by bromodeoxyuridine (BrdU) incorporation, and BrdU-positive cells were counted in the dentate gyrus using confocal microscopy. Results showed that while the rates of hippocampal cell proliferation were comparable between the N2O and sham groups at day 1, levels increased by 1.4 folds at day 7 after one session exposure to N2O. Multiple N2O exposures significantly increased the rate of hippocampal cell proliferation to 2 folds. Therefore, sub-anesthetic doses of N2O, similar to ketamine, increase hippocampal cell proliferation, suggesting that there will ultimately be an increase in neurogenesis. Future studies should investigate added N2O exposures and their antidepressant behavioral correlates.